Control of the critical points for the safety of pasteurized milk in CV Cita Nasional - Aji, Hutama Puranto; Nuhriawangsa, Adi Magna Patriadi; Kartikasari, Lilik Retna (Livestock and Animal Research, 2023)
This study aims to determine the control of critical points in the production of pasteurized milk in CV. Cita Nasional by implementing the Hazard Analysis Critical Control Point (HACCP) system. This research was descriptive qualitative with the aim of exploring the data in depth and specifically. The data collection techniques used were interviews and observation. Interviews were conducted in each part of pasteurized milk Furtherstep was observation techniques to collect data to determine the critical point of pasteurized milk production in all production chains. Control of the critical point of pasteurized milk production in CV. Cita Nasional by determining the source of contamination in each part of production. The source of danger in the mixing process is contamination from tools, workers and the environment. The source of danger in the pasteurization and homogenization process is the pasteurization time and temperature that are not fulfilled. The source of danger in the cooling process is contamination by spore-forming bacteria that do not die during the pasteurization process. Sources of danger during the packaging process come from packaging that is less sterile, contamination from workers and the environment. The source of danger from the distribution process to consumers is product temperature fluctuations and container damage during the shipping process. Control of the critical points for pasteurized milk is carried out by applying SOP and HACCP principles as an effort to prevent and guarantee products that can be consumed in a Safe, Healthy, Whole and Halal (ASUH) way.